Weight on the bar vs. weight on the scale: A qualitative exploration of disordered eating in competitive female powerlifters. (January 2021) - Pereira Vargas, Maria Luisa Fernanda; Winter, Stacy
Abstract: Disordered eating enquiry in sport psychology has arisen due to the need to investigate sub-clinical populations. Weight-class athletes have been found to be 'at-risk' of disordered eating. Therefore, interpretations of experiences can shed light on female weight-class athletes disordered eating accounts. In line with previous interpretive studies, athlete accounts can highlight unique social and cultural insights regarding disordered eating. The aim of the study was to explore disordered eating experiences of female powerlifters. One semi-structured interview was conducted with 17 participants. A thematic analysis resulted in four themes: fear of disclosing weight-cutting concerns; eating like a powerlifter; culture of regulation; and the female body vs. the powerlifter body. Findings highlighted a complex interaction between weight-cutting, the construction of disordered eating, and a female-athlete paradox within powerlifting. We anticipate findings will extend to other weight-class sports, and discuss applied implications for powerlifters' mental health and recommendations for future research. Highlights: Giving a voice to athletes can highlight nuances within disordered eating accounts. 17 female powerlifters provided detailed experiences of disordered eating practices. Themes revealed a complex interaction between weight-cutting and disordered eating. Participants described a paradox between a powerlifting body and a societal body. The psychology of weight-cutting findings may extend to other weight-class sports.